Effects of Sodium-Glucose Transporter 2 Inhibitors (SGLT2-I) in Patients With Ischemic Heart Disease (IHD) Treated by Coronary Artery Bypass Grafting via MiECC: Inflammatory Burden, and Clinical Outcomes at 5 Years of Follow-Up - Sardu, Celestino; Massetti, Massimo; Testa, Nicola; Martino, Luigi Di; Castellano, Gaetano; Turriziani, Fabrizio; Sasso, Ferdinando Carlo; Torella, Michele; De Feo, Marisa; Santulli, Gaetano; Paolisso, Giuseppe; Marfella, Raffaele (Frontiers in Pharmacology, 2021)
Introduction: Minimally invasive extracorporeal circulation (MiEEC) reduced inflammatory burden, leading to best clinical outcomes in patients treated with coronary artery bypass grafting (CABG). Despite this, the patients with type 2 diabetes mellitus (T2DM) vs. those without T2DM (non-T2DM) have a worse prognosis, caused by over-inflammation and modulated by sodium-glucose transporter 2 receptors. However, we evaluated the inflammatory burden and clinical outcomes in non-T2DM vs. T2DM patients under sodium-glucose transporter 2 inhibitors (SGLT2-I users) vs. non-SGLT2-I users at 5 years of follow-up post-CABG via MiECC. Materials and methods: In a multicenter study, we screened consecutive patients with indications to receive CABG. The study endpoints were the inflammatory burden (circulating serum levels of tumor necrosis factor-alpha (TNF α), interleukin 1 and 6 (IL1, IL6), C reactive protein (CRP), and leucocytes count, and the clinical outcomes at follow-up of 5 years in non-T2DM vs. SGLT2-I users, in non-T2DM vs. non-SGLT2-I users, and SGLT2-I users vs. SGLT2-I non-users. Results: at baseline, and at 1 year and 5 years of follow-up, the non-T2DM vs. SGLT2-I users, the non-T2DM vs. non-SGLT2-I users, and SGLT2-I users vs. non-SGLT2-I users had the lowest values of IL-1, IL-6, and TNFα, (p<0.05). At 1 year of follow-up, SGLT2-I users vs. non-T2DM, and non-SGLT2-I users vs. non-T2DM had a higher rate of all-deaths, cardiac deaths, re-myocardial infarction, repeat-revascularization, and stroke, and of the composite endpoint (p<0.05). In a multivariate Cox regression analysis, the composite endpoint was predicted by IL1 [2.068, (1.367-3.129)], and TNFα [1.989, (1.081-2.998)], and by SGLT2-I [0.504, (0.078-0.861)]. Conclusion: in T2DM patients, the SGLT2-I significantly reduced the inflammatory burden and ameliorated clinical outcomes at 5 years of follow-up post CABG via MiECC.